Atomic shell ionization and e+e−-pairs creation at the finite nuclear temperatures - V. M. Kolomietz; S. N. Fedotkin (Ядерна фізика та енергетика)
General expressions for the probabilities of the atomic shell ionization and e+e- -pairs creation at the “heated” nuclei are found. The spectral distributions of the positrons and conversion electrons are investigated in the case of the nuclear E1 -transitions. The temperature dependent conversion coefficients for these processes are obtained.